Long‐term outcomes of sporadic rectal cancer versus ulcerative colitis‐associated rectal cancer: a matched case‐control study. Issue 12 (25th August 2022) - Tatar, Cihad; Lightner, Amy L.; Jia, Xue; Liska, David; Kalady, Matthew; Steele, Scott R.; Gorgun, Emre
Abstract: Background: Although patients with ulcerative colitis (UC) are at increased risk of rectal cancer compared to the general population, it remains unclear whether their oncologic outcomes are different than sporadic rectal cancer (S‐RC).We aimed to compare survival and oncologic outcomes in S‐RC versus UC‐associated rectal cancer (UC‐RC). Methods: We performed a retrospective case‐control study of patients who underwent surgical resection for rectal cancer between 2005 and 2015. Data collected included patient demographics, intraoperative variables, postoperative outcomes, and oncological outcomes. Results: A total of 138 patients were included; 92 patients with S‐RC and 46 with UC‐RC. Both groups were comparable in terms of demographics, oncologic characteristics, oncologic treatment strategies, perioperative complications and operative factors except for preoperative radiotherapy. At a median follow‐up time of 3.7 years the 3‐and 5‐year OS rates; the 1‐and 3‐year DFS rates were comparable between the groups. Conclusion: Ulcerative colitis‐associated rectal cancer patients have similar survival and oncologic outcomes as sporadic rectal cancer patients. Abstract : Ulcerative colitis‐associated and sporadic rectal cancer patients were compared. Survival rates were similar. Oncologic outcomes were similar. Perioperative complications were comparable.